Patrimonio en conserva. Los vínculos indentitarios como clave de aprendizaje en el grado de magisterio - Sofía Marín Cepeda (Midas: Museus e Estudos Interdisciplinares, 2017)
We present the link with objects as a learning key in Artistic Education in Non-formal Spaces, a free optativity module subject in Primary Education Degree at University of Valladolid (Spain). To do this, we began thinking over the reformulation of museum’s functions and spectator’s role, the didactic function of museum and its connections with formal education, to understand its influence in art education classroom, to afford the role of objects in the construction of identities. From the heritage education perspective, people establish links with assets, giving them a certain value. On this basis, we propose our educational proposal around the identity links as a key to raise awareness and generate transferable learning to artistic objects with heritage value. We present the didactic proposal Preserved Heritage, as an example based on the links between students and their most personal heritage, generating artefacts and stories in order to visualize established relationships and transfer learning to broader contexts. Visualization of relationships and links transforms the object experience, transforming the understanding of student’s own artistic creation practices, placing it from a new perspective, more conscious and experiential. In this way, the heritage education vision transforms teaching-learning processes towards a meaningful experience for the students.